THE NATURAL DYNAMICS OF THE DIVERSITY OF SMALL MAMMAL’S COMMUNITIES IN PRIMARY FORESTS IN THE CENTRAL OF THE CASPIAN-BALTIC WATERSHED (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
Diversity is one of the main characteristics of the system, which reflects its complexity and structure. Diversity of biotic communities is always being actively discussed in the consideration of their organization, functioning, and sustainability. However, many questions still remain debatable. The report deals with the results of long-term (1980-2015) studies of the diversity of micromammalia communities in the primary ecosystems of southern Taiga of the Central Forest State Natural Biosphere Reserve (Russia), which is located in the centre of the Caspian-Baltic watershed. The diversity change of small mammals’ communities was connected with climatic trends, extreme and catastrophic climatic phenomena. The authors offer methods of research and evaluation of α - and β-diversity of communities in conditions of the continuum of the environment of primary forests with the use of the gradient approach and GIS analysis.